2020
DOI: 10.1007/978-3-030-37323-8_48
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Joy in the Profession of Critical Care Medicine

Abstract: The Intensive Care Unit (ICU) can be a stressful environment for patients and families, with well-established long-term consequences. The impact that this unique environment can have on healthcare professionals is being increasingly recognized. Challenging ethical situations, exposure to high patient mortality and difficult daily workloads can lead to excessive stress for those caring for critically ill patients. A growing body of literature suggests that this excessive stress and resultant moral distress can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…4,6,7 Crowe et al 8 reported that up to 73% of ICU nurses who cared for patients with COVID-19 demonstrated mild to severe symptoms of posttraumatic stress disorder. Nurse burnout is a significant concern under normal conditions in various health care settings (including ICUs), 9 but it has been even more of a concern during the pandemic.…”
mentioning
confidence: 99%
“…4,6,7 Crowe et al 8 reported that up to 73% of ICU nurses who cared for patients with COVID-19 demonstrated mild to severe symptoms of posttraumatic stress disorder. Nurse burnout is a significant concern under normal conditions in various health care settings (including ICUs), 9 but it has been even more of a concern during the pandemic.…”
mentioning
confidence: 99%